2009
DOI: 10.1108/14769018200900017
|View full text |Cite
|
Sign up to set email alerts
|

Screening Adults with Down's Syndrome for Early Signs of Dementia

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Where indicated, the clinician may consider requesting a computed tomography or magnetic resonance imaging brain scan to further investigate the decline in function (McBrien, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, the clinician may consider requesting a computed tomography or magnetic resonance imaging brain scan to further investigate the decline in function (McBrien, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When there is an SCS increase ≥ 7 and/or an SOS increase ≥ 5, we suggest that a referral for a psychiatric assessment should be made. At this point, there should be consideration of requesting a full health screen and relevant bloods by the general practitioner (McBrien, 2009). This would allow to rule out reversible causes of dementia and delirium, including hypothyroidism, infection and folic acid abnormalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Moran et al (2013) highlights recommendations for the evaluation and management of dementia in adults with intellectual disabilities. Generally of note is that ideally a baseline assessment be conducted at age 30 to capture an individual’s functioning before the potential onset of dementia, followed by reassessment every 2 years for those in their 40s and annually for those aged over 50 (McBrien, 2009). This enables the capturing of an accurate and extensive record of baseline skills’ level in people with intellectual disabilities, which is crucial for regular comparison and key to early diagnosis (Jethwa and Cassidy, 2010; O’Caoimh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Bush and Beail (2004) state that the functioning of each person with an intellectual disability must only be compared to a baseline level taken when the person was healthy. It is suggested that baseline assessments for people with Down's syndrome should be in place at age 30 (Turk et al, 2001;McBrien, 2009). Undertaking a baseline assessment at an earlier age may not be accurate as there is evidence of ongoing neurodevelopment in late adolescence and early adulthood (Carr, 2000) Prospective assessments are carried out at a predefined interval schedule while reactive assessments occur when concerns re possible dementia have been raised.…”
Section: What Are We Trying To Assess and When?mentioning
confidence: 99%